2020
DOI: 10.1002/jsfa.10761
|View full text |Cite
|
Sign up to set email alerts
|

The levels of bioactive ingredients in Citrus aurantium L. at different harvest periods and antioxidant effects on H2O2‐induced RIN‐m5F cells

Abstract: BACKGROUND Citrus aurantium L. (Aurantii fructus) is a multi‐purpose citrus fruit with high medicinal and nutritional value, but currently there are no data that can be used to investigate the appropriate harvest time to obtain high‐quality citrus bioactive ingredients from it. RESULTS Phytochemicals and the levels of the main bioactive ingredients were investigated by ultra high performance liquid chromatography electrospray ionization quadrupole time‐of‐flight mass spectrometry (UHPLC‐ESI‐Q‐TOF/MS). The flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Our results, thus, demonstrated that optimized UAE extraction considerably improves C. aurantium leaf waste utilization. Similar results were observed for increases in the antioxidant enzyme activity of UAE-extracted CALE [8].…”
Section: Optimization Of Variablessupporting
confidence: 85%
See 2 more Smart Citations
“…Our results, thus, demonstrated that optimized UAE extraction considerably improves C. aurantium leaf waste utilization. Similar results were observed for increases in the antioxidant enzyme activity of UAE-extracted CALE [8].…”
Section: Optimization Of Variablessupporting
confidence: 85%
“…However, a large amount of C. aurantium leaves with potential active ingredients are discarded, which may pose an environmental risk [6]. C. aurantium leaf extract (CALE) has substantial antioxidant and antimicrobial properties [7,8]. However, CALE's biological activity often depends on various factors, such as the origin, variety, environmental background (soil texture and degree of fertilization), and maturity stage of C. aurantium; the climate it is cultivated in; and the extraction methods used [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the suitable harvest period for Jiang Aurantii Fructus, with Li et al finding that it should be harvested within 1 week before and after the Major Heat, consistent with the Chinese Pharmacopoeia 32 . Wang et al 11 made similar observations, suggesting that Fructus Ponciri Trifoliatae should be collected in early to mid‐June, 33 Citrus fruit can be appropriately harvested from June to early July, 34 and Chongqing Aurantii Fructus should be collected from mid‐July to early August 35 . However, there are currently no studies on the optimal harvest period for Xiang Aurantii Fructus.…”
Section: Resultsmentioning
confidence: 89%